The Effect of Information Technology and Total Quality Management on Organizational Performance - Sanjaya, Sigit; Mayola, Liga (International Review of Management and Marketing, 2019)
This study discovers the effect of information technology and total quality management (TQM) on organizational performance. The unit of analysis is state-owned enterprises in Padang city, Indonesia. The study utilized primary data which is obtained through the questionnaire. Total sampling is used in this study. 90 questionnaires were returned as a final sample. Data were analyzed by Multiple Regression Analysis performed by SPSS 25 software. The result shows that information technology has a positive and significant effect on organizational performance. Total quality management has a positive and significant effect on organizational performance. Keywords: Information Technology; Total Quality Management; Organizational Performance JEL Classifications: D83, L86, M15 DOI: https://doi.org/10.32479/irmm.8858